Tipping-Curve Calibration of Space-Based Passive Microwave Radiometers. - DiLiberto, Michael. (2017)
Abstract: Recent advances in radio-frequency device technology have enabled the development of miniature passive radiometers with unprecedented reductions in mass, power, and cost. These advances have facilitated the deployment of ultracompact radiometer payloads on "micro-satellites" for Earth remote sensing applications. The micro-satellite approach offers several key advantages for current and emerging Department of Commerce (DOC), National Oceanic and Atmospheric Administration (NOAA), National Aeronautics and Space Administration (NASA), and Department of Defense (DOD) needs, including rapid deployability, fault tolerance, and cost reduction. A major remaining challenge in the practical use of micro-satellites for high-fidelity atmospheric studies is the on-orbit calibration of the radiometer transfer functions, which often depend in a complicated way with the sensor's time-evolving thermal and radiometric states. In this thesis, a new calibration methodology is explored for space-based Earth remote sensing. The tipping-curve calibration scheme, a commonly used ground-based technique, has been adapted for use in space-based systems. A statistical maximum a posteriori estimation technique is used that leverages tipping curve measurements to find calibration parameters. A model-based approach is used to prove the effectiveness of the method.; Thesis (M.S.)--Tufts University, 2011.; Submitted to the Dept. of Electrical Engineering.; Advisors: Eric Miller, and Vincent Leslie.; Committee: Ronald Lasser.; Keywords: Remote sensing, Environmental studies, and Electrical engineering.